The EU AI Act: Law of Unintended Consequences? - Sabrina Kutscher (Technology and Regulation)
After long deliberations, the highly anticipated AI Act is almost there. Although it is yet to be seen what the effects of this landmark regulation are going to be, it is important to already prepare for what can be expected and to identify possible dynamics regarding competencies, implementation, and enforcement. Hence, this article provides a novel perspective of the AI Act by answering the question of what regulatory dynamics can be expected with the AI Act entering the “regulatory space” of AI? The assumption here is that he AIA is entering a “regulatory space” that is already somewhat occupied by various public and private actors which have different relevant regulatory resources, both legal competencies and extra-legal capacities. The aim of this article is therefore a more expansive mapping of actors and their resources, where power and influence is both contingent upon legal competencies and extra-legal capacities, by combining regulation of technology literature with the regulatory space framework.